A commentary on the 2015 Canadian Clinical Practice Guidelines in glutamine supplementation to parenteral nutrition. Issue 1 (December 2015) - Leguina-Ruzzi, Alberto
Abstract Glutamine is one of the conditionally essential free amino acids with multiple biological functions. Its supplementation to parenteral nutrition has been widely used for the management of complications in intensive care. However, controversial clinical reports have generated reluctance in the use of this pharmaco-nutrient. In this commentary, we address the impact of four studies that influenced the recommendations on glutamine supplementation by the Canadian Clinical Practice Guide 2015. Because of the importance of this guideline in clinical practice, we strongly believe that a more rigorous and critical evaluation is required to support recommendations in future guidelines.